2000
DOI: 10.2337/diacare.23.10.1499
|View full text |Cite
|
Sign up to set email alerts
|

Intentional weight loss and mortality among overweight individuals with diabetes.

Abstract: OBJECTIVE: To estimate the effect of intentional weight loss on mortality in overweight individuals with diabetes. RESEARCH DESIGN AND METHODS: We performed a prospective analysis with a 12-year mortality follow-up (1959-1972) of 4,970 overweight individuals with diabetes, 40-64 years of age, who were enrolled in the American Cancer Society's Cancer Prevention Study I. Rate ratios (RRs) were calculated, comparing overall death rates, and death from cardiovascular disease (CVD) or diabetes in individuals with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
353
2
14

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 492 publications
(377 citation statements)
references
References 23 publications
8
353
2
14
Order By: Relevance
“…Weight management 7 , especially correction of abdominal obesity 4,5 , is crucial to obtain a global cardiovascular risk reduction, and previous studies have shown that intentional weight loss is able to reduce overall and CVD mortality in patients with type-2 diabetes. 80 The ongoing CRESCENDO (Comprehensive Rimonabant Evaluation Study of Cardiovascular ENDpoints and Outcomes) RCT will assess whether rimonabant 20 mg can reduce the risk of major CVD events in 17,000 abdominally obese patients with clustering risk factors (at least half with type-2 diabetes) followed for 5 years. 81 …”
Section: Cardiovascular Studiesmentioning
confidence: 99%
“…Weight management 7 , especially correction of abdominal obesity 4,5 , is crucial to obtain a global cardiovascular risk reduction, and previous studies have shown that intentional weight loss is able to reduce overall and CVD mortality in patients with type-2 diabetes. 80 The ongoing CRESCENDO (Comprehensive Rimonabant Evaluation Study of Cardiovascular ENDpoints and Outcomes) RCT will assess whether rimonabant 20 mg can reduce the risk of major CVD events in 17,000 abdominally obese patients with clustering risk factors (at least half with type-2 diabetes) followed for 5 years. 81 …”
Section: Cardiovascular Studiesmentioning
confidence: 99%
“…Agurs-Collins et al (1997) found that weight loss through diet and exercise was significantly greater at 6 months when compared to a control group who received standard diabetes care. Intentional weight loss was also found to be associated with substantial reduction in mortality of overweight individuals with diabetes (Williamson et al, 2000). The amount of weight loss in the intervention group (À2.4 kg) resulted in a significant decrease in hemoglobin Alc (HbAlc) of 2.4%.…”
Section: Introductionmentioning
confidence: 99%
“…However, several clinical trials have documented short-term benefits of weight loss on glycemic control (Williamson et al, 2000;Hermansen et al, 2001). Agurs-Collins et al (1997) found that weight loss through diet and exercise was significantly greater at 6 months when compared to a control group who received standard diabetes care.…”
Section: Introductionmentioning
confidence: 99%
“…The on-going study PROGRESS awarded by the National Prevention Research Initiative hopes to examine the benefits, at several different levels of lifestyle interventions, of weight loss on reducing risk of developing chronic No illness unintentional loss (21) No illness, intentional loss (21) Overweight lost у2 BMI* (22) Obese, lost у2 BMI* (22) Unintentional, overweight, wt lost (23) Unintentional, obese, wt lost (23) Intentional, overweight, wt lost (23) Intentional, obese, wt lost (23) Combined studies (random effect) disease such as cancer, CVD and diabetes. This multidisciplinary approach has six phases, which will be described briefly (for more detail, see Vale et al (29) ): phase 1, systematic reviews; phase 2, qualitative analysis with three group types of focus interviews; phase 3, discrete choice experiment to examine which weight-loss interventions individuals would prefer; phase 4, econometric analysis of large-panel datasets (cancer, CHD and diabetes); phase 5, analysis of cost to the National Health Service of cancer, CHD and diabetes; phase 6, a costbenefit analysis using phases 1-5.…”
Section: Prevent Obesity Grrowing Economic Synthesis Studymentioning
confidence: 99%